GROWTH RATE OF ACROPORA TENUIS CORAL WHICH IS TRANSPLANTED ON DIFFERENT ATTACHMENT MEDIA - Budikusuma, R Arief; Nurhayati, Atikah; Pangaribuan, Nurmala (Jurnal Segara, 2024)
Coral transplantation is the activity of cultivating/breeding coral colonies using the fragmentation method. Several techniques have been used in transplant activities, but knowledge of the right transplantation technique is needed so the activities can run well. This study aims to determine the effect of different types of substrate and attachment media used on the growth rate and survival of Acropora tenuis corals transplanted into three attachment media at Karang Malang beach at a depth of two meters. The research was carried out for four months, March-June 2023 through field research using a randomized block design method with two factors, namely the type of substrate used (cement, coral, clay, glass bottles, cans) and different attachment media (control, cement, epoxy). The results of the analysis showed that the use of cement as a fixing medium was more effective and affected coral growth and the growth rate of Acropora tenuis than epoxy and without adhering media. The highest growth rate was found in cement attachment media, which was 0.62 cm/month, and the lowest in the method without attachment media, namely 0.45 cm/month. While the epoxy sticking method is 0.51 cm/month. The survival rate for cement attachment media was 96%, epoxy adhesion media was 88% and treatment without attachment media/control was 76%.